2014
DOI: 10.1111/bph.12773
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing hydrogen sulfide as a novel anti‐cancer agent by targeting cancer glycolysis and pH imbalance

Abstract: BACKGROUND AND PURPOSEMany disparate studies have reported the ambiguous role of hydrogen sulfide (H2S) in cell survival. The present study investigated the effect of H2S on the viability of cancer and non-cancer cells. EXPERIMENTAL APPROACHCancer and non-cancer cells were exposed to H2S [using sodium hydrosulfide (NaHS) and GYY4137] and cell viability was examined by crystal violet assay. We then examined cancer cellular glycolysis by in vitro enzymatic assays and pH regulator activity. Lastly, intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 66 publications
2
116
2
Order By: Relevance
“…6C) in compensation to inhibition of the mitochondrial function. Supporting our findings, others have also reported that a synthetic H 2 S donor promotes an influx of glucose and triggers enhanced glycolysis in another human breast cancer cell line (31). We then analyzed the decreased proliferation induced by NaHS in the acidic condition.…”
Section: Chronic Nahs Injection Alone Is Inactive To Control Tumor Grsupporting
confidence: 85%
See 1 more Smart Citation
“…6C) in compensation to inhibition of the mitochondrial function. Supporting our findings, others have also reported that a synthetic H 2 S donor promotes an influx of glucose and triggers enhanced glycolysis in another human breast cancer cell line (31). We then analyzed the decreased proliferation induced by NaHS in the acidic condition.…”
Section: Chronic Nahs Injection Alone Is Inactive To Control Tumor Grsupporting
confidence: 85%
“…By noticing that low pHe itself had profound impact on cancer cell proliferation, we questioned whether NaHS treatment was able to exacerbate the acidic stress experienced by cancer cells at low pHe. Indeed, it was recently evidenced that, besides its ability to enhance glycolysis, H 2 S also impairs the activity of pH regulators in cancer cells, leading to the intracellular accumulation of acid and reduction of pHi (31,32). It is also known that pHi must be kept in a narrow range, otherwise cell-cycle progression and biosynthetic processes are compromised (33).…”
Section: Chronic Nahs Injection Alone Is Inactive To Control Tumor Grmentioning
confidence: 99%
“…It has been reported that the increased H 2 S production plays a crucial role in cell proliferation and the related angiogenesis in several types of cancer cell lines, such as colonic and ovarian cancers. 18,19) In addition, there are many papers showing that endogenous or exogenous H 2 S modulates cell proliferation and migration in gastric, oral, breast, pancreas, lung or prostate cancer and also leukemia, 12,[20][21][22] whereas, H 2 S promotes and suppresses cancer growth in distinct cells. Thus, the effects of H 2 S on cancers might vary with the tissues, conditions surrounding cancer, the amount of synthesized H 2 S, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Combined effects leading to increased metabolic acid production, defective pH regulation, and cell death. Lee et al (2014) 5.1. Cardiovascular system: Vascular smooth muscle and platelet function…”
Section: Anticancer Propertiesmentioning
confidence: 99%